Therapeutic communication underlying interpersonal relationship between elementary school adolescent and teacher - Hellen Roehrs; Mariluci Alves Maftum; Maguida Costa Stefanelli (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Descriptive research, qualitative in nature, carried out with 11 teachers from an elementary school in Curitiba/Brazil. Objective: to bring about effective interpersonal relationship between teaching staff and teenage students. Data collection was performed by means of group discussion strategy. Theoretical landmark was Therapeutic Communication by Maguida Stefanelli. Results were presented under the following theme categories: "Communication in the interpersonal relationship between teacher and teenage student"; "The teacher acknowledges the therapeutic function in communication"; "The specificities in teenagers' communication"; they pointed out the relevance to health and education professionals in learning therapeutic communication, specially for those who work with teenagers, in order to make pedagogic relationship and actions more effective, less conflicting and trustworthy. Participants became aware of how important it is to deepen their knowledge on the studied theme for a constructive teaching practice among teenagers.